Early Prediction of Treatment Response to Sorafenib with Elastosonography in a Mice Xenograft Model of Hepatocellular Carcinoma: A Proof-of-Concept Study - Salvatore, V.; Baron Toaldo, M.; Marinelli, S.; Milazzo, M.; Palamà, C.; Venerandi, L.; Cipone, M.; Bolondi, L.; Piscaglia, F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: Sorafenib is the reference therapy for advanced hepatocellular carcinoma (HCC). There is no method for predicting in the early period subsequent individual response. Starting from the clinical experience in humans that subcutaneous metastases may rapidly change consistency under sorafenib and that elastosonography allows assessment of tissue elasticity, we investigated the role of this ultrasound-based technique in the early prediction of tumor response to sorafenib in a HCC mice model.Materials and Methods: HCC subcutaneous xenografting in mice was utilized. Mice were randomized to vehicle (17 mice) or treatment with sorafenib (19 mice). Strain elastosonography (Esaote, Italy) of the tumor mass was performed at different time points (day 0, + 2 and + 14 from treatment start) until the mice were sacrificed (day + 14). At the same time points, the volume was calculated with ultrasonography.Results: Sorafenib-treated mice showed a smaller increase in tumor size on day + 14 in comparison to vehicle-treated mice (tumor volume increase + 175 % vs. + 382 %, p = 0.009). The median tumor elasticity increased in both groups on day + 2 (+ 5.65 % and + 3.86 %, respectively) and decreased on day + 14 (–3.86 % and –3.63 %, respectively). However, among Sorafenib-treated tumors, 13 mice with a growth percentage delta < 200 % (considered as good treatment response) showed an increase in elasticity on day + 2 (+ 8.9 %, range –12.6 – + 64) while the other 6 with a growth percentage delta > 300 % (considered as poor treatment response) showed a decrease in elasticity (–17 %, range –30.2 – + 15.3) (p = 0.044).Conclusion: Elastosonography appears to be a promising noninvasive new technique for the early treatment prediction of HCC tumor response to sorafenib. Specifically, an early increase in tumor elasticity (corresponding to tumors becoming softer) is associated with a good response.
Keywords: ultrasound; animal investigations; treatment effects; tumor